Anxiety of pregnant women with HIV/AIDS during the covid 19 pandemic - Indriastuti, Nur Azizah; Melda, Melda; Oktafia, Riski (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
HIV/AIDS are global health problems that cause a high mortality rate in the world. The high incidence of HIV/AIDS will have an impact on the general population such as pregnant women, because pregnant women are at high risk of transmitting various diseases to their babies. Anxiety during pregnancy will also make pregnant women with HIV/AIDS experience mental health burdens, especially in the current condition, Covid 19 pandemic. The general purpose of this study was to determine the anxiety of pregnant women with HIV/AIDS during the Covid 19 pandemic. This research uses qualitative research methods with descriptive research types. In this study, the researcher used purposive sampling. The sample selected in this study were pregnant women with HIV/AIDS, families and peer support. Researchers used depth interviews to collect data. The results study, researchers found 4 themes, namely the experience of pregnant women while suffering from HIV/AIDS, the perception of pregnant women with HIV/AIDS during the covid 19 pandemic, the influence of HIV/AIDS on pregnancy and social support for pregnant women with HIV/AIDS. The conclusion of this study is pregnant women with HIV/AIDS who have a fear of being exposed to the covid 19 virus because they are a risky group. Abstrak: HIV/AIDS merupakan masalah kesehatan global yang menyebabkan tingginya angka kematian di dunia. Tingginya angka kejadian HIV/AIDS akan berdampak pada masyarakat umum seperti ibu hamil, karena ibu hamil berisiko tinggi menularkan berbagai penyakit kepada bayinya. Kecemasan saat hamil juga akan membuat ibu hamil dengan HIV/AIDS mengalami beban kesehatan mental, apalagi dalam kondisi pandemi Covid 19 saat ini. Tujuan umum dari penelitian ini adalah untuk mengetahui kecemasan ibu hamil dengan HIV/AIDS selama masa pandemi Covid-19. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian deskriptif. Dalam penelitian ini, peneliti menggunakan purposive sampling. Sampel yang dipilih dalam penelitian ini adalah ibu hamil dengan HIV/AIDS, keluarga dan dukungan sebaya. Peneliti menggunakan wawancara mendalam untuk mengumpulkan data. Hasil penelitian, peneliti menemukan 4 tema yaitu pengalaman ibu hamil saat menderita HIV/AIDS, persepsi ibu hamil dengan HIV/AIDS selama pandemi covid 19, pengaruh HIV/AIDS terhadap kehamilan dan dukungan sosial ibu hamil. wanita dengan HIV/AIDS. Kesimpulan dari penelitian ini adalah ibu hamil dengan HIV/AIDS yang memiliki ketakutan terkena virus covid 19 karena merupakan kelompok yang berisiko.